2023
DOI: 10.3390/life13010127
|View full text |Cite
|
Sign up to set email alerts
|

3D-QSAR Studies, Molecular Docking, Molecular Dynamic Simulation, and ADMET Proprieties of Novel Pteridinone Derivatives as PLK1 Inhibitors for the Treatment of Prostate Cancer

Abstract: Overexpression of polo-like kinase 1 (PLK1) has been found in many different types of cancers. With its essential role in cell proliferation, PLK1 has been determined to be a broad-spectrum anti-cancer target. In this study, 3D-QSAR, molecular docking, and molecular dynamics (MD) simulations were applied on a series of novel pteridinone derivatives as PLK1 inhibitors to discover anti-cancer drug candidates. In this work, three models—CoMFA (Q² = 0.67, R² = 0.992), CoMSIA/SHE (Q² = 0.69, R² = 0.974), and CoMSIA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Several research studies have demonstrated that the addition of nitrogen-containing heterocyclic groups, such as thiazole, pyrazole, pyrimidine, thiadiazole, and triazole, to the surface recognition domain of HDACIs, can significantly enhance their selectivity and inhibitory potency [33]. It has been observed that the N, O, and S atoms, along with the electron-rich nitrogen-containing heterocycle, are capable of forming π-π and hydrogen bonding interactions with the amino acid residues located at the periphery of HDAC catalytic sites [34]. Table 2.…”
Section: Molecular Docking Interactionsmentioning
confidence: 99%
“…Several research studies have demonstrated that the addition of nitrogen-containing heterocyclic groups, such as thiazole, pyrazole, pyrimidine, thiadiazole, and triazole, to the surface recognition domain of HDACIs, can significantly enhance their selectivity and inhibitory potency [33]. It has been observed that the N, O, and S atoms, along with the electron-rich nitrogen-containing heterocycle, are capable of forming π-π and hydrogen bonding interactions with the amino acid residues located at the periphery of HDAC catalytic sites [34]. Table 2.…”
Section: Molecular Docking Interactionsmentioning
confidence: 99%
“…In the present work, we use the three-dimensional quantitative structure–activity relationship (3D-QSAR) with the comparative molecular field analysis (CoMFA) and comparative molecular similarity indices analysis (CoMSIA) descriptors to determine the key characteristics for the potential inhibition of MCF-7 cells by tetrahydrobenzo[4,5]thieno[2,3-d]pyrimidine derivatives ( Er-rajy et al, 2022 ; Er-rajy et al, 2023a ). In addition, the ADME-Tox (ADMET) studies and pharmacokinetic characteristics were used to predict the pharmaceutical features of the newly designed molecules for aspects crucial to drug effectiveness and pharmacokinetics, including solubility, permeability, and metabolic stability ( Alqahtani, 2017 ).…”
Section: Introductionmentioning
confidence: 99%